Integrated Small RNA Sequencing, Transcriptome and GWAS Data Reveal microRNA Regulation in Response to Milk Protein Traits in Chinese Holstein Cattle - Cai, Wentao; Li, Cong; Li, Junya; Song, Jiuzhou; Zhang, Shengli (Frontiers in Genetics, 2021)
Milk protein is one of the most important economic traits in dairy industry. Yet, the regulatory network of miRNAs for the synthesis of milk protein in mammary is poorly understood. Samples from twelve Chinese Holstein cows with three high (≥ 3.5%) and three low (≤ 3.0%) phenotypic values for milk protein percentage in lactation and non-lactating were examined through deep small RNA sequencing. We characterized 388 known and 212 novel miRNAs in mammary gland. Differentially expressed analysis detected 28 miRNAs in lactation and 52 miRNAs in the non-lactating period with a highly significant correlation with milk protein concentration. Target prediction and correlation analysis identified some key miRNAs and their targets potentially involved in the synthesis of milk protein. We analyzed for enrichments of GWAS signals in miRNAs and their correlated targets. Our results demonstrated that genomic regions harboring DE miRNA genes in lactation were significantly enriched with GWAS signals for milk protein percentage traits, and that enrichments within DE miRNA targets were significantly higher than in random gene-sets for the majority of milk production traits. This integrated study on the transcriptome and post-transcriptional regulatory profiles between significantly differential phenotype of milk protein concentration provides new insights into the mechanism of milk protein synthesis, which should reveal the regulatory mechanisms of milk secretion.